Prevalence of occupational lung disease among Botswana men formerly employed in the South African mining industry. Issue 1 (January 1997) - Steen, T W; Gyi, K M; White, N W; Gabosianelwe, T; Ludick, S; Mazonde, G N; Mabongo, N; Ncube, M; Monare, N; Ehrlich, R; Schierhout, G
Abstract : OBJECTIVE: To determine whether previous health experiences affect the prevalence of occupational lung disease in a semirural Botswanan community where there is a long history of labour recruitment to South African mines. METHOD: A cross sectional prevalence study of 304 former miners examined according to a protocol including a questionnaire, chest radiograph, spirometry, and medical examination. RESULTS: Overall mean age was 56.7 (range 28-93) years, mean duration of service 15.5 (range 2-42) years. 26.6% had a history of tuberculosis. 23.3% had experienced a disabling occupational injury. Overall prevalence of pnemoconiosis (> 1/0 profusion, by the International Labour Organisation classification) was 26.6%-31.0%, and 6.8% had progressive massive fibrosis (PMF). Many were entitled to compensation under South African law. Both radiograph readers detected time response relations between pneumoconiosis and PMF among the 234 underground gold miners. PMF could result from < 5 years of exposure, but was not found < 15 years after first exposure. Both pulmonary tuberculosis (PTB) and pneumoconiosis were found to be associated with airflow limitation. CONCLUSIONS: Former miners in Botswana have a high prevalence of previously unrecognised pneumoconiosis, indicative of high previous exposures to fibrogenic respirable dust. Their pneumoconiosis went unrecognised because they had no access to surveillance after employment. Inadequate radiographic surveillance or failure to act on results when employed or when leaving employment at the mines could have contributed to under recognition. Community based studies of former miners are essential to fully evaluate the effects of mining exposures. Our findings indicate a failure of established measures to prevent or identify pneumoconiosis while these miners were in employment and show that few of the social costs of occupational lung diseases are borne by mining companies through the compensation system.